2008
DOI: 10.1167/iovs.07-0605
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of the Fine Structure of Rhodamine-Labeled Macaque Retinal Ganglion Cells

Abstract: This in vivo method applied to ganglion cells demonstrates that structures smaller than the somas of typical retinal cells can be accessible in living eyes. Similar approaches may be applied to image other relatively transparent retinal structures, providing a potentially valuable tool for microscopic examination of the normal and diseased living retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…It utilized an AO imaging system (Geng et al 2012;Gray et al 2006Gray et al , 2008 to obtain highresolution images of fluorescing cells in retina despite the challenges of low fluorescence levels and eye movements. We employed an UV light source that activates the S-cone opsin to measure ganglion cell responses in the presence of the blue imaging laser, which also excites M-cone opsin and rhodopsin.…”
Section: Discussionmentioning
confidence: 99%
“…It utilized an AO imaging system (Geng et al 2012;Gray et al 2006Gray et al , 2008 to obtain highresolution images of fluorescing cells in retina despite the challenges of low fluorescence levels and eye movements. We employed an UV light source that activates the S-cone opsin to measure ganglion cell responses in the presence of the blue imaging laser, which also excites M-cone opsin and rhodopsin.…”
Section: Discussionmentioning
confidence: 99%
“…Gray et al showed that individual RGC bodies, axons, and dendrites could be visualized using adaptive optics retinal imaging in living macaque eyes when a fluorescent dye was introduced into RGCs via retrograde transport after injection into the LGN (Figure 6). 21,3 Ganglion cell bodies, axons, and dendrites labeled with eGFP have also been visualized in living rat eyes using FAOSLO. 29 These techniques are too invasive for use in humans, but many of the studies that are particularly relevant for understanding RGC function are perhaps best applied in animal models.…”
Section: Ganglion Cellsmentioning
confidence: 99%
“…However, these contrast with the smooth, bead-free processes of ganglion cell dendrites and axons imaged in vivo (e.g., Gray et al, 2008) and of ganglion cells maintained in organotypic culture . Is bead formation an artifact of tissue processing and, if so, can it be prevented?…”
Section: Introductionmentioning
confidence: 82%